Evaluation of the effectiveness of letrozole in the treatment of experimentally modeled endometriosis in rats. Issue 3 (September 2019) - Yarmolinskaya, Maria; Molotkov, Arsenii
The necessity of finding new drugs for the treatment of endometriosis is stipulated by significant number of recurrences, side effects, and high cost of treatment. Increased activity of aromatase in endometrioid heterotopies is revealed. That is why, aromatase inhibitors may be effective in the treatment of endometriosis. In this study, endometriosis was modeled in rats by autotransplantation of uterine fragments to peritoneum, which was supplemented by ovariectomy and ethinylestradiol replacement therapy. After 14 ± 2 days, laboratory animals underwent laparoscopy to measure formed heterotopies and then the rats were divided into two groups. Nine animals were receiving letrozole (0.5 mg/kg/day) therapy for 3 weeks. The rats of the control group did not receive treatment (n = 11). At the end of the experiment (21 ± 3 days after laparoscopy), re-evaluation and determination of size of heterotopies as well as histological study were carried out in two groups. In all the rats of the main group, treated with letrozole, the decrease in the size of heterotopies was revealed; the percentage of reduction was 79.92% ± 7.89% (p < 0.0001). Growth of all endometriotic foci was observed in the control group. Thus, the use of the aromatase inhibitor letrozole in the treatment of endometriosis is effective.